2010
DOI: 10.1007/s11094-010-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of the combination of magnetohydrodynamic thermochemotherapy and magnetic resonance tomography

Abstract: Fe 3 O 4 nanoparticles were coated with a layer of citric acid, forming coordination bonds between citrate ions and iron ions. The resulting aqueous citrate ferrite colloid was used as a T 2 -weighted MRI negative contrasting agent. Sequential i.v. doses of citrate ferrite and Magnevist led to increases in MRI image contrast for 40 h and brightness for 30 min; scanning using a Bruker Biospec BC 70/30 USR biospectrotomograph yielded enhanced MRI images. This enhancement of MRI images was used to monitor oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The same was done with 30 rats with glioblastoma 101/8. NaCl buffer (0.9 %, 0.5 ml), 20 µl of gadolinium-based contrast agent Magnevist® [3][4][5][6], DF sol (70-250 nm Fe 3 O 4 -γ-Fe 2 O 3 magnetic particles) were intravenously injected in the tail veins of the rats of groups #1, #2 and #3, respectively. The DF solution had solid content of 5% composed of dextran (69-78%) and magnetic nanoparticles (21-28 %) with magnetization of M s =8.5 kA/m and ζ = +15 mW in 0.5 ml of buffer (pH 6.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same was done with 30 rats with glioblastoma 101/8. NaCl buffer (0.9 %, 0.5 ml), 20 µl of gadolinium-based contrast agent Magnevist® [3][4][5][6], DF sol (70-250 nm Fe 3 O 4 -γ-Fe 2 O 3 magnetic particles) were intravenously injected in the tail veins of the rats of groups #1, #2 and #3, respectively. The DF solution had solid content of 5% composed of dextran (69-78%) and magnetic nanoparticles (21-28 %) with magnetization of M s =8.5 kA/m and ζ = +15 mW in 0.5 ml of buffer (pH 6.4).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the research was aimed at early treatment of the centers of glial tumor proliferation. Various tumor therapy methods have been tested such as thermotherapy using iron-oxide magnetic nanoparticles combined with external beam radiotherapy [1], chemo-and thermotherapy [6][7][8][9][10], photodynamic therapy [11,12], etc. Here we present the results on combined photodynamic and magneto-thermo-chemo-therapy that employ chemotherapeutic drugs with dextran-ferrite (DF) magnetic nanoparticles heated by RF magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Ten mice from each of the 2 nd , 3 rd and 4 th groups were injected by 300 µl of a mixture containing 40% CFS (net Fe 3 O 4 weight: 83 mg; CP 40 µg; MX 20 µg; MP 4 µg; pH 7.4). Immediately after the injection, NdFeB magnetic bandage (induction of 0.2 T and gradient of 15 mT/cm) was applied to concentrate the nanoparticles in the tumor tissue [6,[8][9][10]13]. Within 30 minutes at 48º C mice were placed into a 60x200 mm inductor with RF power for MTC with necrotic slime aspiration and a mixture of 0.12 mg DC and 0,054 mg DT was injected IP and IC at metastases of B 16, Са 755 and LLC.…”
Section: Methodsmentioning
confidence: 99%
“…Other anticancer agents have also been explored with this technique. For example, Brusentsov et al demonstrated that by combining a dextran ferrite-and citrate-coated magnetic nanoparticles with melphalan or cyclophosphamide the lifespan of mice increased by 180% and 290%, respectively, with significant tumor remission [53]. The in vitro and in vivo thermopotentiation of geldanamycin, an HSP 90 inhibitor using IONPs was evaluated in a B16 melanoma model [54].…”
Section: Overcoming Multidrug Resistancementioning
confidence: 99%